Little Red Riding Hood - Wurfel, Marlene (My University, 2018)
Tales from the Lilypad's take on the most iconic fairytale of all time: Little Red Riding Hood. Feat. Bluebell the Bluebird as Little Red Riding Hood. And Lily the frog as The Wolf.
Keywords: storytelling; children's stories